Formation of plasma-generated nanostructures on polymer surfaces for various polymer types - Munzert, P.; Praefke, C.; Schulz, U.; Kaiser, N. (International Conference on Plasma Surface Engineering, 2013)
To produce functional elements for optical applications, the components often have to be coated or joined together. Low adhesion is usually caused by different polarity or surface chemistry of the individual components. Therefore, measures have to be taken to modify the respective interfaces to improve the adhesion. In the case of highly transparent polymers (e.g. PC, PMMA, COC, PA) this turns out to be problematic due to the demands on the optical properties. Many methods for adhesion promotion, as etching with chemicals or mechanical roughening, lead to a significant deterioration in the transparency of such components. In many cases a plasma treatment alone has no sufficient effect on improving the adhesion. The Fraunhofer Institute in Jena (IOF) is working several years now on the nano-structuring of polymer surfaces by plasma etching. Except for antireflection purposes, such a structure can also be used to promote adhesion. However, large structure depths and high aspect ratios are necessary therefore. In the experiments carried out here the self-organizing formation of such nanostructures on various polymer types was studied.